Capturing the Effects of Free Surfaces on Threading Dislocation Density Reduction. (8th September 2020) - Bioud, Youcef Ataellah; Boucherif, Abderraouf; Patriarche, Gilles; Drouin, Dominique; Arès, Richard
Abstract : The big concern with using silicon as a substrate for making Ge and III-V devices is the dislocation density in the epilayers. Dislocations degrade device performance by trapping the photo-generated carriers, dragging down efficiency. In this manuscript, a Ge/Si substrate is treated with a post epitaxial process to create a region with a high density of nanovoids within the Ge/Si structure, which acts as a free surface that attracts dislocations, facilitating the subsequent annihilation of their threading arms. Nanovoids are formed in the Ge layer by electrochemical porosification, followed by thermal annealing, creating a new configuration referred to as nanovoid-based Ge/Si virtual substrate (NVS).